2021
DOI: 10.1002/adfm.202102868
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Linear Controllable Synthesis of Mesoporosity in Hierarchical UiO‐66 by Template‐Free Nucleation‐Competition

Abstract: Hierarchies design of porosity in metal-organic frameworks (MOFs) has gained significant interest in recent years, and customization of mesoporous sizes in MOFs is still quite challenging. Herein, a template-free method by nucleation-competition has been developed to realize a near-linear control of the mesopore sizes (3-13 nm) in the hierarchical MOF UiO-66(Hf ). High selectivity of enzyme adsorption, high activity of bulky-molecular catalysis, high stability of mesostructure, and extension to other MOFs furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 47 publications
1
32
0
Order By: Relevance
“…42 In a contrast, we have found that the introduction of water can induce the formation of uniform interparticle mesopores in our previous work. 43 During the solvothermal synthesis of UiO-66, water can accelerate the crystal nucleation via fast hydrolysis of the metal salts and dicarboxylic acid ligands, resulting in the formation of hierarchically micro-/mesoporous UiO-66 NPs. To integrate the acidic site and metal site into HP-UiO-66 (Scheme 1), the phosphotungstic acid Ru salt (Ru 3+ –HPW) was first synthesized via ion exchange of H 3 PW 12 O 40 with RuCl 3 .…”
Section: Resultsmentioning
confidence: 99%
“…42 In a contrast, we have found that the introduction of water can induce the formation of uniform interparticle mesopores in our previous work. 43 During the solvothermal synthesis of UiO-66, water can accelerate the crystal nucleation via fast hydrolysis of the metal salts and dicarboxylic acid ligands, resulting in the formation of hierarchically micro-/mesoporous UiO-66 NPs. To integrate the acidic site and metal site into HP-UiO-66 (Scheme 1), the phosphotungstic acid Ru salt (Ru 3+ –HPW) was first synthesized via ion exchange of H 3 PW 12 O 40 with RuCl 3 .…”
Section: Resultsmentioning
confidence: 99%
“…As listed in Table 1, both CTAB and ClSO 3 H functionalization affected the pore size of the MOFs materials, and the pore size of these porous MOFs increased from 1.71 and 1.38 nm to 3.25 and 7.32 nm after CTAB treatment, respectively. This phenomenon was due to the accumulation of nanomaterials obtained [36,37]. After sulfonic acid functionalization, the acid content of MAS and MCS reached 0.36 and 0.65 mmol (H + )/g, respectively.…”
Section: Characterization Of Catalystsmentioning
confidence: 96%
“…5a. 80 As the amount of H 2 O increases, the crystal size decreases, and thus, the mesopore size decreases. These experiments show that mesopores are beneficial to the adsorption and catalysis of macromolecules.…”
Section: Constructing Strategies At Different Pore Scalesmentioning
confidence: 99%